Preoperative Circulating 11-Oxygenated Androgens Are Associated With Metastasis-free Survival in Localized Prostate Cancer. Issue 2 (14th November 2022) - Dahmani, Cylia; Caron, Patrick; Simonyan, David; Lacombe, Louis; Aprikian, Armen; Saad, Fred; Carmel, Michel; Chevalier, Simone; Lévesque, Eric; Guillemette, Chantal
Abstract : Purpose: Adrenal 11-oxygenated androgens may support cancer progression in men with prostate cancer owing to their abundance and androgenic potential. We hypothesized that preoperative circulating levels of 11-oxygenated androgens influence clinical outcomes in men with newly diagnosed localized prostate cancer. Materials and Methods: We studied 1, 793 treatment-naïve patients and 155 patients who received preoperative treatment with 5α-reductase inhibitors in the prospective PROCURE cohort, for which preoperative plasma samples were obtained prior to radical prostatectomy. Adrenal 11-oxygenated precursors, potent 11-oxygenated androgens and their metabolites (n=7), were quantified using liquid chromatography-tandem mass spectrometry. Circulating levels were evaluated in relation to prognostic factors, disease-free survival, and metastasis-free survival using multivariable Cox proportional hazards models. Results: At a median follow-up of 93.8 months after surgery, 583 patients experienced biochemical recurrence, 104 developed metastatic disease, and 168 deceased. Higher levels of 11-hydroxytestosterone and 11-ketotestosterone were observed in men with PSA >20 ng/mL and positive nodal status ( P < .05). In multivariable analyses, no significant association between 11-oxygenated androgens and disease-free survival was observed. Adrenal 11β-hydroxyandrostenedione, the predominant androgenic 11-ketotestosterone, and its metabolite 11-ketoandrosterone, modeled as quartiles, were associated with metastasis-free survival ( P = .06, P = .03, and P = .008, respectively). Significant accumulation of 11-oxygenated androgen precursors and bioactive androgens, but reduced metabolite levels, was observed in patients on 5α-reductase inhibitors ( P < .001). Conclusions: Preoperative circulating 11-oxygenated androgen levels are associated with metastasis-free survival in men with localized prostate cancer undergoing radical prostatectomy and are affected by 5α-reductase inhibitor treatment.